Hedge algebraic approach in construction the language scale for assessment - Sơn, Trần Thái; Hồ, Nguyễn Cát (Journal of Computer Science and Cybernetics, 2012)
This paper presents methods of formulating the semantic 4-tuple approach basing on Hedge algebra used in case assessment scale which is a subset of the term set of lengths less than a given number k